2017
DOI: 10.1016/j.amjmed.2016.08.046
|View full text |Cite
|
Sign up to set email alerts
|

Future of the Palliative Care Workforce: Preview to an Impending Crisis

Abstract: BACKGROUNDThe specialty of palliative care has experienced remarkable acceptance over the last decade, with teams present in 85% of medium/large hospitals in the US. 1 For many serious illnesses like cancer, advanced heart disease, stroke, and chronic obstructive pulmonary disease, routine integration of palliative care is considered standard of care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
118
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 202 publications
(119 citation statements)
references
References 2 publications
0
118
0
1
Order By: Relevance
“…A survey of palliative care clinicians by the American Academy of Hospice and Palliative Medicine revealed that almost half intend to leave the field by 2023 secondary to retirement, burnout, and dissatisfaction with organization/practice. [18] Current estimates reveal 6600 board-certified palliative care physicians in practice and fewer than 250 fellowship-trained physicians entering the field every year. [18] There is a cap on the number of CMS-funded graduate medical education positions, leaving programs to rely on philanthropy and other mechanisms to fund palliative care fellows.…”
Section: Cancer and Palliative Care Workforcementioning
confidence: 99%
See 2 more Smart Citations
“…A survey of palliative care clinicians by the American Academy of Hospice and Palliative Medicine revealed that almost half intend to leave the field by 2023 secondary to retirement, burnout, and dissatisfaction with organization/practice. [18] Current estimates reveal 6600 board-certified palliative care physicians in practice and fewer than 250 fellowship-trained physicians entering the field every year. [18] There is a cap on the number of CMS-funded graduate medical education positions, leaving programs to rely on philanthropy and other mechanisms to fund palliative care fellows.…”
Section: Cancer and Palliative Care Workforcementioning
confidence: 99%
“…[18] Current estimates reveal 6600 board-certified palliative care physicians in practice and fewer than 250 fellowship-trained physicians entering the field every year. [18] There is a cap on the number of CMS-funded graduate medical education positions, leaving programs to rely on philanthropy and other mechanisms to fund palliative care fellows. [19] The projected shortage of palliative care physicians to meet the current demands is substantial.…”
Section: Cancer and Palliative Care Workforcementioning
confidence: 99%
See 1 more Smart Citation
“…Improving integrated PC is critical because there are limited PC fellowship training programs for physicians in the US, with fewer than 250 graduates per year and an estimated shortage of 18,000 PC physicians [3]. To address the need for more integrated PC, many leaders, academics, and organizations have called for the institution of high-quality PC across the health care spectrum.…”
Section: Improving Palliative Care Deliverymentioning
confidence: 99%
“…PC clinicians are tasked with reducing the suffering of these patients and face daily challenges, such as treating patients with intractable pain, facilitating end-of-life (EOL) decision making, and collaborating with other health care specialists to ensure that PC is sufficiently integrated [2]. A recent survey found that PC physicians who were planning to leave the profession commonly cited burnout or dissatisfaction with their organization or practice as the reason [3], and another study found that high moral distress is linked to clinicians' intentions to leave their current position [4]. Moral distress has been described as "one or more negative self-directed emotions or attitudes that arise in response to one's perceived involvement in a situation that [one] perceives to be morally undesirable" [5].…”
Section: Introductionmentioning
confidence: 99%